2010
DOI: 10.5194/cp-6-415-2010
|View full text |Cite
|
Sign up to set email alerts
|

The Southern Hemisphere semiannual oscillation and circulation variability during the Mid-Holocene

Abstract: Abstract. The Paleoclimate Modelling Intercomparison Project (PMIP) was undertaken to assess the climatic effects of the presence of large ice-sheets and changes in the Earth's orbital parameters in fully coupled Atmosphere-Ocean General Circulation Models (AOGCMs). Much of the previous literature has focussed on the tropics and the Northern Hemisphere during the last glacial maximum and Mid-Holocene whereas this study focuses only on the Southern Hemisphere. This study addresses the representation of the Semi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 41 publications
1
9
1
Order By: Relevance
“…Application of the same anomalies to the Mid-Holocene follows uniformitarian principles that suggest similar changes would result in climate regime shifts over longer time periods. Ackerley and Renwick (2010) found that the strongest changes in the SH circulation occurred in SON and MAM, and were associated with the sea-surface temperature response to the changes in insolation shown in Fig. 2.…”
Section: Eof Procedures For Synotic Classificationmentioning
confidence: 91%
See 2 more Smart Citations
“…Application of the same anomalies to the Mid-Holocene follows uniformitarian principles that suggest similar changes would result in climate regime shifts over longer time periods. Ackerley and Renwick (2010) found that the strongest changes in the SH circulation occurred in SON and MAM, and were associated with the sea-surface temperature response to the changes in insolation shown in Fig. 2.…”
Section: Eof Procedures For Synotic Classificationmentioning
confidence: 91%
“…The aims of this study, therefore, are to provide a first step for assessing SH circulation patterns as represented by a set of GCMs that cover the Mid-Holocene, using the synoptic climate regime classification method of Kidson (2000) and then comparing those results to palaeoclimate proxy data within the New Zealand sector to see if the models and prox-ies agree. Ackerley and Renwick (2010) have already shown that the seasonal SH mid-latitude circulation is sensitive to differences in the Earth's orbital paramaters during the Mid-Holocene, which cause changes in seasonal insolation (see Fig. 2).…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…Analyses of PMIP2 simulations suggest the occurrence of significant changes in global and regional atmospheric circulation, precipitation and temperature, including the Southern Hemisphere. In fact, Ackerley and Renwick (2010) describe decreased (increased) sea level pressure during the MH compared to PI times over polar-subpolar regions and inverse conditions at middle latitudes of the Southern Hemisphere during austral spring (autumn) with a spatial pattern of anomalies similar to the structure of the Southern Annular Mode. These anomalies of atmospheric circulation were also detected by Rojas and Moreno (2011).…”
Section: Introductionmentioning
confidence: 91%
“…The sea level pressure (SLP) in high and lower latitudes of the Southern Hemisphere has long been known to be dominated by a second harmonic because the circumpolar trough moves meridionally twice a year in the three ocean basins [ van Loon, 1967; van Loon and Jenne, 1972;Raphael, 2004;Ackerley and Renwick, 2010]. The SLP north of 50°S thus has lowest values in May-June-July (MJJ) and November-December-January (NDJ) when the trough of low pressure moves northward, while farther south around Antarctica the minima are in February-March-April (FMA) and August-September-October (ASO) when the trough contracts and intensifies [ van Loon, 1967van Loon, , 1972; van Loon and Rogers, 1984].…”
Section: Introductionmentioning
confidence: 99%